An introduction to regional planning : concepts, theory and practice - Glasson, John (London : Hutchinson, 1978)
This is a general and introductory text in regional planning with particular reference to United Kingdom.
Includes index.
Includes bibliographical references: p. 411-415.
lje 16/05/2018
Loans
Keywords: Regional planning; United Kingdom